ALK Inhibitors, a Pharmaceutical Perspective - Galvani, Arturo; Ardini, Elena (Frontiers in Oncology, 2012)
In 2007, the ALK tyrosine kinase was described as a potential therapeutic target for a subset of non-small-cell lung cancer patients. Clinical proof of concept, culminating in the recent approval by the Food and Drug Administration of the Pfizer drug crizotinib followed in record time. The drug was approved together with a companion diagnostic for detection of patients eligible for therapy. This remarkable example of the coming of age of personalized medicine in cancer therapy is hopefully only an auspice of things to come in a rapidly developing field. Perhaps unsurprisingly, however, the appearance of clinical acquired resistance to crizotinib was observed early on in clinical testing, with the identification of several ALK secondary point mutations which diminish drug efficacy and which open the way for development of second-generation inhibitors. It is also emerging that acquired resistance to crizotinib may additionally occur through ALK-independent mechanisms, which still need to be elucidated in detail. Here we discuss the factors that led to such a rapid approval of a targeted agent, and we describe the second-generation compounds currently in development.